The GLP-1 receptor agonist exendin-4 reduces taurine and glycine in nucleus accumbens of male rats, an effect tentatively involving the nucleus tractus solitarius - Edvardsson, Christian E.; Vestlund, Jesper; Ericson, Mia; Jerlhag, Elisabet (Frontiers in Pharmacology, 2024)
The physiological effects of glucagon-like peptide-1 (GLP-1) are mainly centered on its ability to decrease blood glucose levels and facilitate satiety. Additional physiological functions have been identified by means of GLP-1 agonists such as exenatide (exendin-4; Ex4). In particular, Ex4 reduces the intake of natural and artificial rewards, effects that to some extent involve activation of GLP-1 receptors in the nucleus tractus solitarius (NTS). Although Ex4 acts in the brain, the neurochemical mechanisms underlying this activation are not fully elucidated. Investigating Ex4-induced neurochemical alterations in the nucleus accumbens (NAc) would be valuable for understanding its impact on reward-related behaviors. The aim of the present exploratory in vivo microdialysis study was therefore to study how Ex4, administered either systemically or locally into the NTS, influences classical neurotransmitters like dopamine, serotonin, noradrenaline, glutamate and GABA as well as additional players such as glycine, taurine and serine in NAc of male rats. We showed that Ex4 reduced extracellular levels of serine, taurine and glycine, where the latter two declines appear to involve activation of GLP-1R in the NTS. Besides, after systemic Ex4 injection the metabolites DOPAC, HVA, and 5HIAA are elevated. Where the increase in metabolites related to dopamine, but not serotonin, involves GLP-1 receptors in other areas than the NTS. Although the descriptive nature of the present data does not provide causality, it may however serve as an indication of mechanisms underlying how Ex4 may modulate reward-related behaviors.